Securing human resources for Japan’s aging population: a mixed methods study of job satisfaction and well-being among Southeast Asian long-term care workers in Japan - Igarashi, Niaya Harper; Kiriya, Junko; Carandang, Rogie Royce; Ong, Ken Ing Cherng; Shibanuma, Akira; Jimba, Masamine (BMC health services research, 2024)
Background Japan is one of the countries experiencing a “super-aged society.” The government has looked to Southeast Asia for recruiting workers to fill the demand for long-term care (LTC) workers. However, migrant LTC workers have faced many job-related stressors. This study aimed to examine the factors associated with job satisfaction and subjective well-being among Filipino, Indonesian, and Vietnamese LTC workers in Japan and explore the specific factors behind what makes them satisfied in their jobs. Methods A convergent mixed methods study was conducted. The workers were recruited through snowball and convenience sampling and completed a self-administered questionnaire for the quantitative part. The association of the work environment with the workers’ job satisfaction and subjective well-being were analyzed using multiple linear regression analysis. An interpretive phenomenological approach was used to conduct in-depth interviews of the workers, which were analyzed using a deductive and inductive approach for the qualitative part. Quantitative and qualitative results were integrated and interpreted to expand on the findings with new insights. Results In the final analysis, 122 workers were included (20 Filipino, 43 Indonesian, and 59 Vietnamese). In the quantitative part, having the necessary tools/equipment (Unstandardized Coefficient [B] = 16.1, 95% Confidence Interval [CI] = 6.8, 25.3) and support from work (B = 18.1, 95% CI = 8.6, 27.6) were associated with a higher level of job satisfaction. Having experienced harassment on the job was associated with a lower level of job satisfaction (B = -18.2, p = 0.007, 95% CI = -28.5, -7.8). There is no strong evidence for the association with subjective well-being. In the qualitative part, prominent themes emerged related to cultural sensitivity and an inadequate knowledge of caring for older adults living with dementia. The integrated findings suggested inadequate and unequal Japanese language training across the facilities. Moreover, the importance of human relations in the workplace emerged, with some workers desiring a deeper connection with their Japanese coworkers. Conclusions A supportive and culturally sensitive work environment may bring about more motivated employees and increase employee retention from migrant LTC workers. Government and facilities should consider policies supporting a culturally sensitive work environment and more equitable Japanese language training across all facilities.